2008
DOI: 10.1111/j.1365-2567.2007.02728.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MMP‐2 and MMP‐9 secretion from T helper 0, 1 and 2 lymphocytes alone and in coculture with macrophages

Abstract: Summary Metalloproteinases (MMPs) participate in extracellular matrix remodelling and regulatory signalling during chronic inflammatory states such as atherosclerosis formation. However, the sources and mediators of MMP upregulation need clarification. We investigated whether proinflammatory mouse T helper type 1 (Th1) lymphocytes are more active in MMP secretion than naïve Th0 or anti‐inflammatory Th2 phenotypes, in the absence of specific antigenic stimulation, under baseline conditions and after contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 41 publications
2
46
2
Order By: Relevance
“…Further upregulation of MMP-9 expression by LPS in human macrophages is only modest 47,61,63 or even absent 57 ; CD40L and ox-LDL are also ineffective. 51,59,67,68 MMP-9 expression is not upregulated in rabbit in vivo generated foam cells compared with nonfoamy macrophages. 51 Moreover human macrophage and rabbit foam cell MMP-9 expression is not affected by adenovirus-mediated overexpression of the inhibitory subunit of NF-B, IB␣.…”
Section: Constitutive Upregulation Independent Of Nf-bmentioning
confidence: 98%
“…Further upregulation of MMP-9 expression by LPS in human macrophages is only modest 47,61,63 or even absent 57 ; CD40L and ox-LDL are also ineffective. 51,59,67,68 MMP-9 expression is not upregulated in rabbit in vivo generated foam cells compared with nonfoamy macrophages. 51 Moreover human macrophage and rabbit foam cell MMP-9 expression is not affected by adenovirus-mediated overexpression of the inhibitory subunit of NF-B, IB␣.…”
Section: Constitutive Upregulation Independent Of Nf-bmentioning
confidence: 98%
“…14 Our experiments confirm this previous observation in MN and show for the first time that 1a,25(OH) 2 D 3 also regulates MMP-7 and MMP-10 expression in MN under basal conditions and/or during M. tuberculosis infection. As previous studies have suggested that an interaction between T cells and MN/macrophages enhances MMP expression by both cell populations 11,[22][23][24][25] we also investigated the effects of 1a,25(OH) 2 D 3 on MMP regulation in a mixed population of adherent and non-adherent PBMC. Our observation that each MMP analysed had higher constitutive expression in PBMC than in MN led us to investigate the influence of 1a,25(OH) 2 D 3 and M. tuberculosis on MMP secretion and activity in PBMC.…”
Section: Discussionmentioning
confidence: 99%
“…CD40L can stimulate endothelial cells to express adhesion molecules that accelerate the adhesion of macrophages to endothelial cells, which are responsible for inflammation and the initiation of atherosclerosis [16,17,18]. Furthermore, CD40L induces matrix metalloproteinase overexpression, which promotes atherosclerotic plaque rupture [19]. …”
Section: Introductionmentioning
confidence: 99%